INVESTMENT ACTIVITY OF MOTOR TRANSPORT ENTERPRISES IN UKRAINE - Рябоштан, Людмила (SWorldJournal, 2021)
This paper is devoted to a comparative assessment of the state and trends of development of the transport industry and motor transport enterprises in Ukraine in the context of substantiation of ways for improving the mechanism of investment controlling of